Disparidades regionais da produção e dependência espacial das emissões de gases do efeito estufa do consumo de lenha no Brasil - Pereira, Josicleide de Moura (2024)
Firewood, historically integrated into the Brazilian energy matrix, not only represents an important energy source to meet economic demands, but also contributes to sustainability and socioeconomic development. This dissertation analyzed regional disparities in the production and spatial dependence of Greenhouse Gas (GHG) emissions resulting from the consumption of firewood in Brazil. To this end, a literature review of bioenergy was carried out under the aspects of forest biomass; analyzed the regional concentration of firewood production in Brazil and analyzed the spatial dependence of GHG emissions resulting from the consumption of firewood in the country. The methodologies used included a systematic literature review, locational indicators, concentration and exploratory analysis of spatial data. The main results revealed a sample of 47 articles for systematic literature review, distributed in 23 countries, with Brazil and the United States being the ones that published the most. There was a tendency for the production of firewood from plant extraction to be concentrated in the North and Northeast Regions, while firewood from forestry was concentrated in the intermediate regions of the South, Southeast and Central-West Regions. In spatial analyses, high GHG emissions and high neighborhood consumption of firewood were observed. This pattern was identified both for plant extractivism in part of the intermediate regions of the Northeast region, especially in the states of Rio Grande do Norte, Ceará and Bahia, and for forestry in the intermediate regions of the South Region and some of the Southeast region. This dissertation provided an understanding of the regional and spatial aspects of the use of firewood and its emissions, being able to guide actions and public policies to promote the sustainable use of firewood in Brazil.